Effectiveness of bylaws related to sustainable intensification of potatoes in Southwestern Ugandan - Makuma-Henry, M. (Makerere University, 2024)
Only one-third of global farms utilise sustainable agriculture. This study examined the bylaws' existence, interaction, implementation, and effectiveness in facilitating sustainable potato crop intensification (SCI) in South Western Uganda. An exploratory sequential research design involved 22 key informants’ interviews, six focus group discussions and 104 potato farmers who responded to a questionnaire. Qualitative and quantitative data were analysed using Atlas.ti 7.5.16 and Stata 13.0. Thematic content analysis was used for qualitative data. Descriptive statistics and multivariate linear regression were used for quantitative data. The study findings revealed positive complementary interactions between formal and informal bylaws to achieve SCI. There was complementary and accommodating interaction between formal and informal bylaws in achieving SCI. The physical environment and socioeconomic conditions posed challenges as well as opportunities for developing and strengthening bylaws. Farmers’: knowledge of bylaws (p = 0.03); participation (p = 0.01), location (p = 0.03); gender (p = 0.001); other occupations (p = 0.01), income (p = 0.02) interaction with local councils to implement bylaws (p = 0.01); and knowledge on soil and water conservation bylaws (p = 0.03) were significantly associated with bylaw implementation. Bylaw effectiveness is mostly manifested in the principles of layered multilayers and participation. The majority of potato farmers (63.46%) reported that the bylaws were ineffective. Implementation of improved and quality seed bylaws was significantly associated with effectiveness (p<0.043). In conclusion, farmers acknowledged a number of formal and informal bylaws. Formal and informal bylaws positively interacted with and benefited potato farmers by providing better seeds, potato yields, prices, and higher incomes. Individual and community factors are vital in bylaw implementation, though limited by their congestion and farmers’ engagement in other activities. The study recommends enhancing positive bylaw interaction by engaging communities and local government, creating awareness amongst potato farmers on bylaws, empowering women, and formalising informal bylaws.